Exploring critical thinking processes of a field independent elementary student with low self efficacy in numeracy problem solving - Yustitia, Via; Patmaningrum, Agustin; Yekti, Sherly Mayfana Panglipur; Sari, Nurul Husnah Mustika; Erdyna Dwi Etika (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to describe the critical thinking abilities of elementary school students with a field independent cognitive style and low self efficacy innumeracy problem solving. The study focuses on how students demonstrate critical thinking through clarification, strategy selection, and inference when addressing mathematical tasks.Method: A qualitative research approach was employed to gain an in-depth understanding of students thinking processes. The participants consisted of eight fifth grade students from SDN Ketintang II, selected through purposive sampling. Data were collected using the Group Embedded Figure Test (GEFT) to identify cognitive styles, self efficacy questionnaires to determine affective characteristics, numeracy tests, and semi-structured interviews. The data were analyzed through qualitative procedures, including data reduction, data display, and conclusion drawing. To ensure data credibility, technique triangulation and time triangulation were applied.Findings: The findings reveal that students with a field-independent cognitive style and low self efficacy were able to meet the three critical thinking indicators used in this study. Students demonstrated the ability to identify relevant information during the clarification stage, select appropriate strategies to solve numeracy tasks, and draw conclusions based on the information obtained.However, although these students tended to solve problems independently without seeking assistance from teachers or peers, they frequently expressed uncertainty regarding the accuracy of their answers, even when applying familiar solution strategies.Significance: This study provides insight into the interaction between cognitive style and self efficacy in shaping students’ critical thinking during numeracy activities in elementary mathematics learning. The findings suggest that strong cognitive independence does not automatically lead to high confidence in problem solving, highlighting the importance of integrating affective support alongside cognitive strategy instruction in elementary mathematics learning.